Academic perspectives in high school students in the food and beverage field: Motivations, difficulties and support needs - Esteban, Torres-Zapata Ángel; Leticia, Zarza-García Addy; Esther, Castillo-Ortega Sara; Patricia, Acuña-Lara Juana; Jesús, Brito-Cruz Teresa Del; Pablo, Sánchez-Domínguez Juan (Edelweiss Applied Science and Technology, 2025)
Technical preparatory schools in Mexico, particularly those in the food and beverage sector, face challenges such as limited resources and institutional barriers, despite using a competency-based educational model that integrates theory and practice. This research aims to analyze the academic perspectives of high school students in this area, focusing on their motivations, difficulties, and support needs. Using a mixed-methods approach, a validated questionnaire was applied to new students entering a technical preparatory school in Ciudad del Carmen, Campeche, between August 20 and September 20, 2024. Data were analyzed using SPSS 25.0 and Microsoft Office, employing descriptive statistics and qualitative analysis to identify patterns and draw conclusions. Of 108 students, 89.81% completed the assessment satisfactorily, with the majority being women (55.67%) and an average age of 15.03 years. Overall academic performance was rated as “Good,” with Language and Communication being the most preferred subject (52.58%). The most common study methods were reading and summarizing (62.89%). Regarding motivation, 77.32% pursued personal and professional goals, and 62.89% prioritized extracurricular activities. Although 68.04% reported positive well-being, areas for improvement were noted in infrastructure, academic support, and communication, emphasizing the need for a balanced environment. Effective high school education requires personalized teaching methods and emotional support.